The microcopepod family Oncaeidae: state of knowledge and perspectives. - Böttger-Schnack, R. & D. Schnack (Marine Biology, 2023)
Since the discovery of the frst oncaeid copepod described by Philippi in 1843 as Oncaea venusta, great progress has been achieved regarding the morphological/descriptive taxonomy of the microcopepod family Oncaeidae, occurring in all great oceans and all depth layers of the ocean. The species diversity of this family is still underestimated and the ecological role of oncaeids within the marine ecosystem is not yet well understood, but the life strategy appears to be fundamentally diferent from most other pelagic microcopepod families. The present paper aims at a comprehensive review of the current state of knowledge of this microcopepod family, including taxonomic and phylogenetic issues, questions of species identifcation, specifc morphological and molecular genetic characteristics, information on regional and vertical distribution and abundance, motion behaviour, feeding and food relationships, reproduction aspects, biomass and elemental composition, respiration and metabolic rates. Relevant open questions are highlighted, and examples are given of shortcomings and high uncertain?ties in results of current attempts to include oncaeid copepods in various aspects of global marine ecosystem studies. It is concluded that continued support of taxonomic research is required for Oncaeidae and other small copepod species, based on an integrated approach of morphological and molecular genetic methods and user-friendly regional identifcation keys, to allow an adequate consideration of oncaeids in advanced ecological studies and to achieve a better understanding of the ecological role of this abundant microcopepod family in marine ecosystems.